Data structures and algorithm analysis in Java - Weiss, Mark Allen (Boston, Massachusetts : Pearson Education, 2012)
Data Structures and Algorithm Analysis in Java is an (3z(Badvanced algorithms(3y (Bbook that fits between traditional CS2 and Algorithms Analysis courses. In the old ACM Curriculum Guidelines, this course was known as CS7. This text is for readers who want to learn good programming and algorithm analysis skills simultaneously so that they can develop such programs with the maximum amount of efficiency. Readers should have some knowledge of intermediate programming, including topics as object-based programming and recursion, and some background in discrete math. As the speed and power of computers increases, so does the need for effective programming and algorithm analysis. By approaching these skills in tandem, Mark Allen Weiss teaches readers to develop well-constructed, maximally efficient programs in Java. Weiss clearly explains topics from binary heaps to sorting to NP-completeness, and dedicates a full chapter to amortized analysis and advanced data structures and their implementation. Figures and examples illustrating successive stages of algorithms contribute to Weiss$1 (Bcareful, rigorous and in-depth analysis of each type of algorithm. A logical organization of topics and full access to source code complement the text$1 (Bs coverage.s
1. Introduction -- 2. Algorithm analysis -- 3. Lists, stacks, and queues -- 4. Trees -- 5. Hashing -- 6. Priority queues (heaps) -- 7. Sorting -- 8. The disjoint set class -- 9. Graph algorithms -- 10. Algorithm design techniques -- 11. Amortized analysis -- 12. Advanced data structures and implementation.
Includes bibliographical references and index.
Keywords: DATA STRUCTURES (COMPUTER SCIENCE)